Pengaruh Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Achmad Agus Priyono (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The purpose of this study was to determine the effect of the variable Quality of Work Life on Employee Performance with Job Satisfaction as an intervening variable. The data in this study are primary data obtained by giving questionnaires to employees of the T.U.K PG section. Malang Grand Garden. Data analysis used is linear regression and path analysis. The results of data analysis showed that 1) there was a positive and significant influence between the quality of work life (X) on employee performance (Y)., 2) there was a positive and significant influence between the variables of the quality of work life (X) on job satisfaction (Z), 3 ) there is a positive and significant effect between the variables Job Satisfaction (Z) on Employee Performance (Y) and 4) Job Satisfaction (Z) mediates the relationship between the quality of work life (X) on Employee Performance (Y).